The in Vitro Bioactive Properties of Fermented Brewer's Spent Grain With Lactiplantibacillus plantarum: Aerobic vs Anaerobic Processes - Ha, Minh Quoc; Rimbault, Victor; Nguyen, Phuc Hanh; Berthevas, Mathilde; Ghamsary, Maryam; Kitundu, Eileen; Kam, Rothman; Seale, Brent; Henier Bang-Berthelsen, Claus; Le, Thao (MDPI, 2025)
Introduction Fermentation offers a sustainable method to convert food by-products into valuable resources. This study explored the Lactiplantibacillus plantarum (L. plantarum) fermentation of brewer’s spent grain (BSG), a major by-product from blonde wheat (WB) and stout beer (SB) production. This study compared aerobic and anaerobic fermentation conditions to enhance BSG’s bioactive properties. Methods BSG from WB and SB was fermented with L. plantarum under aerobic and anaerobic conditions for 10 days, with non-fermented BSG as a control. Extracts, collected every two days, were evaluated for in vitro bioactivities: antioxidant capacity (ferric ion reducing antioxidant power (FRAP) and DPPH assays), antimicrobial effects (against Staphylococcus aureus, Escherichia coli, and Bacillus cereus), anti-obesity potential (anti-lipase activity), and cytotoxicity on RAW 264.7 macrophages. Ex vivo antibacterial activity was assessed on wheat- and milk-based food products. Results Fermentation significantly enhanced BSG bioactivities compared to non-fermented controls, with distinct outcomes varying by condition. Anaerobic fermentation doubled antioxidant activity in WB and SB extracts by Day 6 compared to aerobic conditions. Aerobic fermentation showed superior antimicrobial activity, fully inhibiting Bacillus cereus at 83.3 mg/mL (vs. 166.6 mg/mL under anaerobic conditions, Day 6), and stronger anti-obesity effects, with IC₅₀ values of 8.6 mg orlistat equivalents (OE)/g (WB) and 6.6 mg OE/g (SB) on Day 8. Ex vivo assays confirmed antimicrobial effects, with wheat-based media requiring lower concentrations (0.042 mg/mL) than milk-based media (333.3 mg/mL). Cytotoxicity assays indicated no toxicity, with both conditions promoting macrophage proliferation. Conclusions Fermentation with L. plantarum significantly enhances BSG’s bioactivity. Anaerobic conditions optimise antioxidant properties, while aerobic conditions favour antimicrobial and anti-obesity effects. These findings suggest fermented BSG’s potential for food preservation and health-promoting applications.
Keywords: Fermentation; Brewer's Spent Grains; in vitro bioactivities